1998
DOI: 10.1046/j.1365-2249.1998.00613.x
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of orbital T cells in thyroid-associated ophthalmopathy

Abstract: SUMMARYThyroid-associated ophthalmopathy (TAO) has a major effect on the two compartments of the retroorbital (RO) space, leading to enlargement of the extraocular muscles and other RO tissues. T lymphocyte infiltration of RO tissue is a characteristic feature of TAO and there is current interest in whether these T cells are specifically and selectively reactive to RO tissue itself. We recently established 18 T cell lines (TCL) from RO adipose/connective tissue of six patients with severe TAO by using IL-2, an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
35
0
1

Year Published

2000
2000
2018
2018

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 78 publications
(39 citation statements)
references
References 43 publications
3
35
0
1
Order By: Relevance
“…Although the percentage of CD4 + T cells was only significantly higher in patients with hyperthyroid GD the percentage of its subset expressing ICAM-1 was considerably increased in GO group. In agreement with that, the subset of CD4 + T cells was found to predominate in the orbit infiltration in GO [16,17]. After antigen recognition, CD4 + T lymphocytes could secrete cytokines that amplify the immune reaction by either activating CD8 + T lymphocytes or autoantibody-producing B cells [18].…”
Section: Figsupporting
confidence: 81%
“…Although the percentage of CD4 + T cells was only significantly higher in patients with hyperthyroid GD the percentage of its subset expressing ICAM-1 was considerably increased in GO group. In agreement with that, the subset of CD4 + T cells was found to predominate in the orbit infiltration in GO [16,17]. After antigen recognition, CD4 + T lymphocytes could secrete cytokines that amplify the immune reaction by either activating CD8 + T lymphocytes or autoantibody-producing B cells [18].…”
Section: Figsupporting
confidence: 81%
“…We have demonstrated that the percentage of CD8 -/IFN-Á + T cells and the ratio of CD8 -/IFN-Á + T (Th1) cells to CD8 -/IL-4 + T (Th2) cells were markedly higher in early GO patients than in GD patients and the healthy individuals, indicating that the balance of Th1/Th2 shifts to Th1 dominance in early GO (1,2). CD4 + /IFN-Á + T cells secrete IFN-Á which represents Th1-type cytokines, while CD4 + /IL-4 + T cells secrete IL-4 representing Th2-type cytokines (5).…”
Section: Discussionmentioning
confidence: 99%
“…It is believed that factors such as genes, autoimmunity, alteration of orbital fibroblast activity, environmental factors and smoking are intimately correlated to the pathogenesis of GO. The CD3 + CD4 + CD8 -T lymphocytes are predominant in the T cells derived from orbital tissues and peripheral blood of patients with GO (1,2). Previous investigations reported that T cell-mediated immune reactions by Th1 cells might predominate in the orbit in early GO, whereas humoral immunity and Th2 cells may play a greater role in the later stages of the disease (3).…”
Section: Introductionmentioning
confidence: 99%
“…Orbital inflammation in early GO is dominated by a T-helper 1 (Th1) cytokine environment with abundant production of cytokines such as IL-1β, IL-2, IFN-γ and TNF-α while in late GO a Th2 dominated cytokine environment with increased production of IL-4, IL-5 and IL-10 might be more prominent [2,27,28,29]. Of these it has been shown that IL-1β stimulates orbital fibroblasts to produce IL-6, IL-8, CCL2, CCL5 and IL-16, which are chemoattractants for B-lymphocytes, neutrophils, monocytes and T-lymphocytes [30,31].…”
Section: The Pathophysiology Of Gomentioning
confidence: 99%